2014
DOI: 10.1155/2014/619398
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Collagen Cross-Linking with and without Epithelial Removal: A Contralateral Study with 0.5% Hypotonic Riboflavin Solution

Abstract: Purpose. Our main purpose was to compare safety and efficacy in the treatment of progressive keratoconus with “epithelium-on” and “epithelium-off” corneal collagen cross-linking (CXL). Our secondary purpose was to evaluate efficacy of CXL when hypotonic 0.5% riboflavin is used as photosensitizer. Methods. One eye of 20 patients with bilateral progressive keratoconus was randomly treated for “epithelium-on” CXL (group 1) while the fellow eye underwent “epithelium-off” CXL (group 2). Hypotonic 0.5% riboflavin wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 42 publications
(63 reference statements)
1
42
0
4
Order By: Relevance
“…The intact epithelium prevents riboflavin penetration [45] (the large molecular weight of riboflavin being responsible for this). Even the use of higher-concentration (0.5 %) riboflavin solution through the intact epithelium may not facilitate improved results in comparison to the standard (0.1 %) concentration [46].…”
Section: Corneal Collagen Cross-linking For Presbyopia: a Novel Approachmentioning
confidence: 99%
“…The intact epithelium prevents riboflavin penetration [45] (the large molecular weight of riboflavin being responsible for this). Even the use of higher-concentration (0.5 %) riboflavin solution through the intact epithelium may not facilitate improved results in comparison to the standard (0.1 %) concentration [46].…”
Section: Corneal Collagen Cross-linking For Presbyopia: a Novel Approachmentioning
confidence: 99%
“…Studies comparing TE CXL with standard CXL using randomized control trials have shown improvement in both Kmax and BCVA in both protocols. However, the change and stabilization was observed more and prolonged in those treated with standard CXL 22. Since the results of both TE and standard CXL are comparable, TE CXL offers a trade-off between better safety profile and clinically acceptable efficacy.…”
Section: Discussionmentioning
confidence: 97%
“…24,25 Even higher concentration (0.5%) riboflavin solutions may not facilitate improved results in comparison with the standard (0.1%) concentration. 26 The second issue is epithelial and Bowman membrane absorption/filtering of UV-A that could lead to lesser energy delivered to riboflavin-saturated stroma, as effective absorption by riboflavin at the superficial layers inhibits UV-A transmission. 27 Some studies indicate approximately onethird epithelial UV-A absorption, 24 whereas other studies suggest that human corneal epithelium and the underlying basement membrane absorb strongly only at wavelengths less than 310 nm.…”
Section: Discussionmentioning
confidence: 99%
“…30 There is thus inconclusive evidence in the peer-reviewed literature on the aspect of efficacy of some epithelium-on CXL variations. 3,8,26,31,32 The in situ riboflavin application naturally overcomes the first of the 2 obstacles, related to riboflavin penetration through the intact epithelium and in acting as a "blocking" agent against UV-A propagation. This is because the epithelium and Bowman layer, that the UV-A light has to transcend, are not soaked in riboflavin.…”
Section: Discussionmentioning
confidence: 99%